2019
DOI: 10.1002/adma.201806991
|View full text |Cite
|
Sign up to set email alerts
|

NIR Biosensing of Neurotransmitters in Stem Cell‐Derived Neural Interface Using Advanced Core–Shell Upconversion Nanoparticles

Abstract: Non-destructive neurotransmitter detection and real-time monitoring of stem cell differentiation are both of great significance in the field of neurodegenerative disease and regenerative medicine.Although luminescent biosensing nanoprobes have been developed to address this need, they have intrinsic limitations such as autofluorescence, scattering, and phototoxicity. However, upconversion nanoparticles (UCNPs) have gained increasing attention for various biomedical applications due to their high photo-stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 50 publications
0
68
0
1
Order By: Relevance
“…[ 16 ] Utilizing physical stimuli, we also demonstrated that an application magnetic field manipulated physical uncaging of RGD‐presenting nanomaterials to temporally switch the regulation of cell adhesion. [ 17 ] Light [ 18 ] has been typically utilized to trigger photo‐induced chemical changes in the molecular structure utilizing photolabile molecules [ 19 ] or photoisomerization. [ 20 ] A recent study showed the feasibility of utilizing ultraviolet (UV) light to trigger UV‐mediated photocleavage of molecules to modulate the adhesion of macrophages via spatial photo‐patterning strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Utilizing physical stimuli, we also demonstrated that an application magnetic field manipulated physical uncaging of RGD‐presenting nanomaterials to temporally switch the regulation of cell adhesion. [ 17 ] Light [ 18 ] has been typically utilized to trigger photo‐induced chemical changes in the molecular structure utilizing photolabile molecules [ 19 ] or photoisomerization. [ 20 ] A recent study showed the feasibility of utilizing ultraviolet (UV) light to trigger UV‐mediated photocleavage of molecules to modulate the adhesion of macrophages via spatial photo‐patterning strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Research by Haro-González and co-workers demonstrates that the total fluorescence intensity of nanoparticle group not only depends on the number of particles, but also on the direction of the excitation polarization and the orientation of the UCNPs. studies obtained in the last decades are performed by a cluster of nanoparticles, which is quite different from that of an individual particle.…”
mentioning
confidence: 99%
“…studies obtained in the last decades are performed by a cluster of nanoparticles, which is quite different from that of an individual particle. [9,10] Research by Haro-González and co-workers demonstrates that the total fluorescence intensity of nanoparticle group not only depends on the number of particles, but also on the direction of the excitation polarization and the orientation of the UCNPs. [11] Unfortunately, a major obstacle for practical application of UCNPs at single particle level is still their weak luminescence.…”
mentioning
confidence: 99%
“…In addition to the Au nanoparticle, other nanomaterials have been used for neurotransmitter detection. UCNPs played the role of fluorescence emission, and graphene oxide exhibited the quenching effect in this system [64]. These particles are connected to each other by the π-π interaction of dopamine aptamer, and the dopamine could induce the dissociation of graphene oxide from the aptamer by the aptamer-dopamine binding event.…”
Section: Metallic Nanoparticle-based Fluorescence Sensing Strategies mentioning
confidence: 89%
“…If the MNP is composed of noble elements such as Au and Ag, the emitted light is not generated, which we call the quenching effect. On the other hand, emission light can be generated if the nanoparticle acceptors have fluorescent properties such as quantum dot (QD) and upconversion nanoparticle (UCNP) [63,64]. For activation of this phenomenon, there is a specific condition between fluorescent donor and acceptor.…”
Section: Metallic Nanoparticle-based Fluorescence Sensing Strategies mentioning
confidence: 99%